Explaining the UKPDS Legacy Effect - Vinall, Phil (MD Conference Express, 2012)
Ten years of follow-up observations from the United Kingdom Prospective Diabetes Study (UKPDS) demonstrated virtually identical HbA1C levels in subjects who were randomly assigned to 2 different glucose control strategies (intensive or conventional). However, subjects who received intensive glucose control remained at a significantly lower risk of diabetic complications. This article discusses data that examined the degree to which historical HbA1C values contribute to later reductions in the risks of myocardial infarction and all-cause mortality.